OPTIMASI RUTE DISTRIBUSI UNTUK PENGHEMATAN BIAYA DENGAN MENGGUNAKAN METODE SAVING MATRIX DI PT. BANGUN PUTRA KARAWANG STORAGE SUKANDA DJAYA - Karsono, Bambang; Immawan, Taufiq; P, A. Dwi Wahyuni; Padhil, Ahmad (Journal of Industrial Engineering Management, 2025)
The world of education, in this case universities, can be seen as service providers, while students are seen as service users. Students are the most important element for educational institutions, listening to whether the services provided are in accordance with their expectations. Education payment services or what is often referred to as SPP/BPP are financial transactions or payments made by students with the aim of supporting educational development activities. The purpose of this researchis to assist tertiary institutions in improving the quality-of-service quality by analyzing the priority of improvements that must be carried out immediately along with the corrective steps. Based on theresearch results, it is known that the proposed service system specifications for tertiary institutions are in accordance with the needs of students. some of the attributes proposed are(1) Payment procedures, (2) The concept of payment with experience benefits, (3) Service systems, and (4) Service response.